The Influence of Influencers and Brand Image on Adidas Shoe Purchase Decisions Among Generation Z in Surabaya - Claudio Huke; Tias Andarini Indarwati (Lavish Opulent Education, 2026)
This study aims to analyze the influence of influencers and brand image on Adidas shoe purchase decisions among Generation Z in Surabaya. The population of this study consists of Generation Z consumers in Surabaya who have purchased Adidas shoes. The sampling technique used purposive sampling with criteria including respondents aged 12–27 years, having purchased Adidas shoes in the last year, actively using social media, and following influencers who promote Adidas products. A total of 120 respondents participated in this study. Data were collected through an online questionnaire using a Likert scale. The data were analyzed using multiple linear regression analysis. The results show that influencers have a positive and significant influence on purchase decisions. Similarly, brand image also has a positive and significant effect on purchase decisions. These findings indicate that influencers and brand image play an important role in influencing Generation Z consumers in purchasing Adidas shoes. The practical implications suggest that Adidas should collaborate with credible influencers and continuously strengthen its brand image through product innovation, quality consistency, and values that resonate with Generation Z such as creativity, inclusivity, and sustainability